PERANCANGAN APLIKASI TRACKING KAPAL NELAYAN PESISIR BERBASIS ANDROID - Rici Rikardo; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2022)
Indonesia is a maritime country, in the Moro sub-district it is very rare for fishermen to have private boats, there is a system of cooperation between fishermen and ship owners. the existence of this cooperation system makes it difficult for ship owners to monitor their ships, ship owners monitor their ships by contacting fishermen one by one, this activity takes a long time and the location data provided by fishermen is not accurate because it is only based on instinct and experience of fishermen. To make it easier for ship owners to easily monitor their boats without disturbing the activities of fishermen, therefore this study designed an Android-based coastal fisherman tracking application, Android is software used on mobile devices. With a smartphone that is equipped with GPS can help implement this application on a smartphone. The software used in building this application is Android Studio to build Android applications, Visual Studio Code to design APIs, and XAMPP to run a local server. Testing this application using blackbox testing so that all features in the application run as expected. With this application, it is easier for ship owners to monitor their ships and reduce disturbances to fishermen while at sea.